The Effect of Leverage, Total Assets Turnover, and Profitability on Financial Distress in Food and Beverage Subsector Companies on the IDX - Qathrunnada, Novia; Ahmad, Gatot Nazir; Yusuf, Muhammad (LPPPIPublishing, 2024)
This study aims to examine the effect of Leverage, Total Assets Turnover, and Profitability on Financial Distress in Food and Beverage Companies on the IDX. The independent variables in this study are leverage, total assets turnover, and profitability. The dependent variable in this study is financial distress which uses the proxy, namely Negative Net Income. The number of samples in this study amounted to 20 companies with five years of observation so that there were 100 total observations to be analysed. The sampling technique used purposive sampling method. The research method used in this research is quantitative. Data sourced based on secondary data, namely annual reports published from each company. The analysis method used is logistic regression with E-Views. The results of this study indicate that leverage has no effect on financial distress. The total assets turnover variable has no effect on financial distress. Profitability variable has a negative effect on financial distress.